Qadianism between legitimacy and controversy: a study on the of tensions and reactions in Indonesia - Ishak, Mohd. Shuhaimi (s.n, 2012)
It attempts to study on Qadianism in Indonesia which includes religious practices and propagation of belief in the midst of Muslim communities. It will trace the origin of the movement from historical perspective and their arrival in the country. The other aspect of is also related with the nature of doctrine, theological concept and their attitudes toward Islamic religion. Moreover, it will highlight their appeal and demand to be legitimized at the equal footing with other religions namely Islam, Christianity, Buddhism and Hinduism especially after the emergence of what so-called reformative government which is characterized by openness and democratization.